2020
DOI: 10.3389/feart.2020.00083
|View full text |Cite
|
Sign up to set email alerts
|

Antiquity of “Sail-Backed” Neural Spine Hyper-Elongation in Mammal Forerunners

Abstract: Neural spine hyper-elongation in tetrapods is a unique morphological adaptation that creates a dorsal sail. While this extreme morphology has appeared several times in the evolutionary history of tetrapods, it was first experimented with by the nonmammalian synapsid paraphyletic group known as "Pelycosaurs," famously represented by the Permian apex predator Dimetrodon. Here we provide new fossil data tracing the evolution of this morphological innovation back to the initial Carboniferous radiation of the synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Although interesting, the latest iteration of varanopids as diapsids requires additional investigation, and we therefore prefer to consider them as synapsids. Interestingly, among early amniotes, only synapsids appear to have evolved elongated neural spines, as seen here ( Mann & Reisz, 2020 ).…”
Section: Discussionsupporting
confidence: 68%
“…Although interesting, the latest iteration of varanopids as diapsids requires additional investigation, and we therefore prefer to consider them as synapsids. Interestingly, among early amniotes, only synapsids appear to have evolved elongated neural spines, as seen here ( Mann & Reisz, 2020 ).…”
Section: Discussionsupporting
confidence: 68%
“…An alternative suggestion was, however, provided in this same study: that the signal was genuine and reflected the earlier adoption of herbivory in synapsids and their radiation into this new niche (Modesto et al, 2015). Mann and Reisz (2020) alternatively suggested that elongation of neural spines, a trait limited to synapsids until the Mesozoic, may have contributed to the success of synapsids relative to reptiles, whether as a thermoregulatory device giving a metabolic advantage or as a mode of intraspecific recognition aiding reproductive success.…”
Section: Introductionmentioning
confidence: 82%
“…The earliest diversification of amniotes during the Pennsylvanian (late Carboniferous) and Cisuralian (early Permian) are characterized by faunas that are generally considered synapsed-dominated. During this interval, a paraphyletic grouping of basally diverging synapsed families known as pelycosaurs (non-therapsid synapsids) have been described in the published literature since 1940 as dominating in terms of abundance, species richness and morphological diversity (e.g., Romer and Price, 1940;Kemp, 2006;Sahney et al, 2010;Benton, 2012;Brocklehurst et al, 2013;Mann and Reisz, 2020) with reptiles being considered the less diverse lineage until the radiation of archosauromorphs in the Mesozoic (Bakker, 1977;Benton et al, 2004;Ezcurra and Butler, 2018). By the end of the Carboniferous, synapsids are suggested to have outnumbered reptiles approximately two to one, in terms of both raw taxonomic counts and lineage counts from timescaled phylogenies (Reisz, 2003;Modesto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They most likely represent presacrals 8-31, based on the presence of a complete series of 31 presacrals in the holotype. The presence of hatchet-shaped, anteroposteriorly elongated neural spines is unique among most basal eureptiles and more closely resembles that of some early synapsids (Carroll and Baird, 1972;Reisz, 1972;Mann and Paterson, 2019;Mann and Reisz, 2020). In the better-preserved neural spines, the distinct "ball peened" sculpture that characterises the holotype is also present (Carroll and Baird, 1972).…”
Section: Comparative Osteologymentioning
confidence: 97%